A time relic: a new species of dwarf boa, Tropidophis Bibron, 1840 (Serpentes: Amerophidia), from the Upper Amazon Basin - H. Mauricio Ortega-Andrade; Alexander Bentley; Claudia Koch; Mario H. Yánez-Muñoz; Omar M. Entiauspe-Neto (European Journal of Taxonomy, 2022)
The amerophidian snake radiation is a Late Cretaceous superfamily that encompasses two families: Aniliidae, pipe snakes, and Tropidophiidae, dwarf boas. We describe a new dwarf boa snake species, from the Tropidophiidae family, from the cloud forest in northeastern Ecuador. Tropidophis cacuangoae sp. nov. can be diagnosed from its congeners based on external and osteological morphology. The new species inhabits eastern tropical piedmont and lower evergreen montane forests, in the Amazon Tropical Rainforest biome, and is likely to be an Ecuadorian endemic. We also discuss the relationships of the new species with South American tropidophiids and provide a key to the identification of mainland South American dwarf boas.